2023
DOI: 10.1088/1361-6560/acc635
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Monte Carlo simulated absorbed-dose-to-water inside a custom SPECT/CT phantom using active and passive dosimeters: a feasibility study using 99mTc

Abstract: OBJECTIVE: This project aims to provide a novel method for performing dosimetry measurements on TRT radionuclides using a custom-made SPECT/CT compatible phantom, common active and passive detectors, and Monte Carlo simulations. In this work we present a feasibility study using 99mTc for a novel approach to obtaining reproducible measurements of absorbed dose to water from radionuclide solutions using active and passive detectors in a custom phantom for the purpose of benchmarking Monte Carlo-based absorbed do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…A cylindrical, acrylic phantom introduced in previous work (Bertinetti et al 2023) and shown in figure 1, was used for the experiments presented here. The phantom was designed to approximate measurement conditions that may be seen in an RPT dosimetry measurement where the target lesion (source cavity), would be surrounded by tissue (water surrounding the insert in the phantom).…”
Section: Phantom Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cylindrical, acrylic phantom introduced in previous work (Bertinetti et al 2023) and shown in figure 1, was used for the experiments presented here. The phantom was designed to approximate measurement conditions that may be seen in an RPT dosimetry measurement where the target lesion (source cavity), would be surrounded by tissue (water surrounding the insert in the phantom).…”
Section: Phantom Descriptionmentioning
confidence: 99%
“…The detector was chosen because it is already commonly used in clinical practice and was readily available for this investigation. Additionally, the detector is unshielded and is a pre-irradiated, p-type, silicon diode that exhibits relatively little angular, dose rate, and energy dependence when compared to some other commercially available diode detectors (Ralston et al 2012, Bertinetti et al 2023. The construction of the diode is an important factor in its overall behavior.…”
Section: Iba Efd Diodementioning
confidence: 99%